2012
DOI: 10.1037/a0028503
|View full text |Cite
|
Sign up to set email alerts
|

Memory of gender and gait direction from biological motion: Gender fades away but directions stay.

Abstract: The delayed discrimination methodology has been used to demonstrate a high-fidelity nondecaying visual short-term memory (VSTM) for so-called preattentive basic features. In the current Study, I show that the nondecaying high VSTM precision is not restricted to basic features by using the same method to measure memory precision for gait direction and gender-stereotypical gait patterns from high-level point-light walkers. Nondecaying VSTM of direction was found for delays up to 9 s whereas memory for gender dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Such a finding is in line with prior studies, which have reported a loss in visual memory accuracy over time (e.g. Hesse & Franz, 2010;McKeown et al, 2014;Morey & Bieler, 2013;Poom, 2012;Ricker & Cowan, 2010Salmela et al, 2010). Nonetheless, the overall impact of the retention interval remains uncertain and future studies may benefit from employing a range of delaysstronger effects of time with Fribble stimuli have been found after 10 s gaps (Mercer, 2014).…”
Section: Retroactive Interference In Visual Short-term Memorysupporting
confidence: 90%
“…Such a finding is in line with prior studies, which have reported a loss in visual memory accuracy over time (e.g. Hesse & Franz, 2010;McKeown et al, 2014;Morey & Bieler, 2013;Poom, 2012;Ricker & Cowan, 2010Salmela et al, 2010). Nonetheless, the overall impact of the retention interval remains uncertain and future studies may benefit from employing a range of delaysstronger effects of time with Fribble stimuli have been found after 10 s gaps (Mercer, 2014).…”
Section: Retroactive Interference In Visual Short-term Memorysupporting
confidence: 90%
“…Using PLDs as stimuli of interest, a very recent study elegantly explored the WM storage of gender and gait direction information from BM stimuli. Poom (2012) found that direction information can be well kept for 9 s, yet gender information decayed by that time. To our knowledge, the current study is the second study to explore the WM mechanisms for meaningful BM stimuli.…”
Section: Discussionmentioning
confidence: 97%
“…By using point-light displays as stimuli, we recently demonstrated that working memory can hold up to three or four BM stimuli (Shen et al, 2014). Current research has begun to investigate the mechanisms of maintaining BM represen tations in working memory, such as the frame of reference for retaining a BM stimulus in working memory (Wood, 2010), re hearsal mechanisms for BM in working memory (Gao, Bentin, & Shen, 2014), and retaining gait and gender information of BM in working memory (Poom, 2012).…”
mentioning
confidence: 99%